2012
DOI: 10.1186/1477-7819-10-9
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic factors of resected non-small cell lung cancer with chest wall invasion

Abstract: BackgroundWe retrospectively reviewed the clinical features and surgical outcomes of patients with a surgically resected NSCLC invading chest wall in order to identify prognostic factors that impact long term survival.MethodsBetween January 1990 and December 2009, 107 patients who underwent surgical resection for chest wall invading NSCLC were reviewed. Tumors invading only the parietal pleura were defined as superficial invasions, and those involving the soft tissue or ribs were defined as deep invasions.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 20 publications
2
48
1
1
Order By: Relevance
“…This number differs from the data reported by Chapelier et al in 2000 and Lee et al in 2012, who observed a median survival time of 15.9 and 18 months, respectively [13,22]. However, Suzuki et al [23] reported a mean follow-up time of 49.3 months (range, 1 to 207 months).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This number differs from the data reported by Chapelier et al in 2000 and Lee et al in 2012, who observed a median survival time of 15.9 and 18 months, respectively [13,22]. However, Suzuki et al [23] reported a mean follow-up time of 49.3 months (range, 1 to 207 months).…”
Section: Discussionmentioning
confidence: 57%
“…However, the cumulative survival rates at 5 years reported by Lee et al [13] and Kawaguchi et al [6] for cohorts who underwent the different surgical techniques were 26.3% and 44.9%, respectively. Several factors have an impact on the survival of NSCLC patients, of which mediastinal lymphadenopathy is regarded as one of the most important [3,28].…”
Section: Discussionmentioning
confidence: 99%
“…[4]. Однако ряд авторов сообщают о влиянии глубины инвазии на продолжитель-ность жизни больных [5,6].…”
Section: Discussionunclassified
“…NSCLC patients, particularly in the case of chest wall invasion (Doddoli et al, 2005;Wakelee et al, 2005;Lee et al 2012;Mantovani et al, 2012).…”
Section: 7559 Number Of Mediastinal Lymph Nodes As a Prognostic Factmentioning
confidence: 99%